STUDY LITERATURE REVIEW ADVOKASI KEBIJAKAN KESEHATAN MENTAL - Salwa Nurfaiziya; Sinta Ningrum; Heru Nurasa; Enjat Munajat (Journal Publicuho, 2021)
Mental health is a condition that affects a person's thinking, feeling, and protecting yourself so you can succeed in your daily life. However, the amount of stigma and ignorance of the rights of mental health sufferers makes support groups want to carry out policy advocacy. The author conducted a study literature review on mental health policy advocacy that has been done by previous researchers to find out various programs or ways to advocate for mental health management. This SLR shows that advocacy efforts can be carried out by distributing content on social media, communicative discussions, and health literacy tools. Increasing mental health support for policy advocacy will make the government wiser towards mental health policies and also facilitate health services for people with mental disorders.